2012
DOI: 10.1111/j.1745-6584.2012.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Control During Aquifer Storage Recovery Cycle Tests in the Floridan Aquifer

Abstract: Implementation of aquifer storage recovery (ASR) for water resource management in Florida is impeded by arsenic mobilization. Arsenic, released by pyrite oxidation during the recharge phase, sometimes results in groundwater concentrations that exceed the 10 µg/L criterion defined in the Safe Drinking Water Act. ASR was proposed as a major storage component for the Comprehensive Everglades Restoration Plan (CERP), in which excess surface water is stored during the wet season, and then distributed during the dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 26 publications
(31 reference statements)
0
32
0
Order By: Relevance
“…Water quality improvements include the inactivation of pathogens , a reduction in nutrient concentrations , or degradation of organic chemicals , including personal care products . However, subsurface storage can also have deleterious effects on the quality of groundwater that is available for recovery and reuse, through increases in the concentration of major ions and salinity , metals and metalloids , and hydrogen sulfide .…”
Section: Introductionmentioning
confidence: 99%
“…Water quality improvements include the inactivation of pathogens , a reduction in nutrient concentrations , or degradation of organic chemicals , including personal care products . However, subsurface storage can also have deleterious effects on the quality of groundwater that is available for recovery and reuse, through increases in the concentration of major ions and salinity , metals and metalloids , and hydrogen sulfide .…”
Section: Introductionmentioning
confidence: 99%
“…ASR systems have some disadvantages. Surface waters may react with aquifer geology affecting water quality, resulting in high concentrations of alpha radioactivity and arsenic (Mirecki ). ASR has been field‐tested in south Florida; however, a recent review of the large‐scale viability of this storage technology has not proven feasible at the scale envisioned in Comprehensive Everglades Restoration Plan (CERP; SFWMD, USACE ).…”
Section: Restoration Optionsmentioning
confidence: 99%
“…Previous analysis of ASR by the ACOE, with its consultants (Mirecki, Bennett & Lopez-Balaez, 2013), was scientifically flawed because it failed to consider preferential flow through fractures and did not even acknowledge the presence of fractures associated with that ASR site. This deficiency occurred despite the fact that two documents (ACOE, 2004c; produced by the agency of the senior author in that evaluation (Mirecki et al, 2013) identified multiple data sets of lineaments representing fractures in southern Florida, including the vicinity of the Kissimmee River. The influence of heterogeneous flow in the Floridan aquifer system influences ASR injections and withdrawals (Hutchings, Vacher, & Budd, 2004).…”
Section: Asr Analysis and Groundwater Modelingmentioning
confidence: 99%
“…The influence of heterogeneous flow in the Floridan aquifer system influences ASR injections and withdrawals (Hutchings, Vacher, & Budd, 2004). More specifically, none of the fractures in the vicinity of the ASR well at the single ASR site analyzed by Mirecki et al (2013), in the vicinity of the Kissimmee River, were identified or monitored in the study, no extensive monitoring network was established in the Kissimmee River. In fact, neither this nor any of the other ASR tests evaluated in our study included isotopic analysis, trilinear chemical analysis or tracer analysis, such as those described by Bacchus et al (2014), Davies et al (2004), Fetter (1988), Freeze and Cherry (1979), Kincaid et al (2004), Kincaid, Davies, Werner, and DeHan (2012), Schindel et al (2004) and Wilcox, Solo-Gabriele and Sternberg (2004), of the ambient ground water, injected water or "recovered" water at the ASR sites.…”
Section: Asr Analysis and Groundwater Modelingmentioning
confidence: 99%